THE URGENCY OF ISLAMIC MORAL EDUCATION DURING EARLY CHILDHOOD IN THE PERSPECTIVE OF HADITH - Alfiah Nursangadah Saputri; Zulkipli Lessy; Eni Siskowati; Rahmat Illahi (Jurusan Ilmu Hadis Fakultas Ushuluddin, Dakwah dan Adab UIN Sultan Maulana Hasanuddin Banten, 2022)
Education plays an important role in determining the goodness and badness of humans, and Islamic ethics (akhlaq) is the main standard of human quality. In this view, those are an indicator of the success or failure in education. Islamic ethics and moral are essentially a basic value in assessing the nature of a person. The level of education is sometimes not an absolute measure of the tranquility of one's life, but shows how Islamic ethics or moral plays out. For this reason, at an early age children should learn about religion and be provided with a guide for their moral development. The purpose of this study is to find out how the urgency of Islamic ethics education on early childhood and how the hadith illustrates this in children. The research employs the research library method as it depends on investigating written resources such as journals and books. The results of this study showed that Islamic ethics education must be required to begin at an early age because childhood is the most appropriate period to instill good habits. The hadith narrated by Bukhari Muslim on Islamic ethics education in children demonstrates that parents have an important role and contribute significantly in implanting moral values in their children. There are two factors that influence Islamic ethics development in children. First, internal factor includes the innate such as physical, intellectual, and the potential of spirituality. Second, external factors encompass roles of the parents at home, teachers at school, and community leaders in society.